De l’iconoclasme à la censure - Liliane Inés Cuesta Davignon (Les Cahiers de l'École du Louvre)
Traditionally a hetero-patriarchal institution, the museum helps to maintain gender roles, stereotypes and the rendering of women invisible in history. As a legitimising, sacred, public and heteronormative space, the museum has been the target of a series of violent acts that call the institution itself into question. This paper analyses acts that have two things in common: they occur in the museum space and they are motivated by a gender- or sexuality-linked claim, denouncing the situation experienced by women, their absence, the inequalities they suffer, and the visual suppression of sexual minorities. The forms taken by these acts vary. Taking specific examples, four types of acts committed by both men and women are identified: acts of iconoclasm, artistic performances, demonstrations or protests, and acts of censorship.